Effect of Hydraulic Retention Time on Biogas Production from Cow Dung in A Semi Continuous Anaerobic Digester - Agus Haryanto; Sugeng Triyono; Nugroho Hargo Wicaksono (Center of Biomass & Renewable Energy, Diponegoro University, 2018)
The efficiency of biogas production in semi-continuous anaerobic digester is influenced by several factors, among other is loading rate. This research aimed at determining the effect of hydraulic retention time (HRT) on the biogas yield. Experiment was conducted using lab scale self-designed anaerobic digester of 36-L capacity with substrate of a mixture of fresh cow dung and water at a ratio of 1:1. Experiment was run with substrate initial amount of 25 L and five treatment variations of HRT, namely 1.31 gVS/L/d (P1), 2.47 gVS/L/d (P2), 3.82 gVS/L/d (P3), 5.35 gVS/L/d (P4) and 6.67 gVS/L/d (P5). Digester performance including pH, temperature, and biogas yield was measured every day. After stable condition was achieved, biogas composition was analyzed using a gas chromatograph. A 10-day moving average analysis of biogas production was performed to compare biogas yield of each treatment. Results showed that digesters run quite well with average pH of 6.8-7.0 and average daily temperature 28.7-29.1. The best biogas productivity (77.32 L/kg VSremoval) was found in P1 treatment (organic loading rate of 1.31 g/L/d) with biogas yield of 7.23 L/d. With methane content of 57.23% treatment P1 also produce the highest methane yield. Biogas production showed a stable rate after the day of 44. Modified Gompertz kinetic equation is suitable to model daily biogas yield as a function of digestion time.Article History: Received March 24th 2018; Received in revised form June 2nd 2018; Accepted June 16th 2018; Available onlineHow to Cite This Article: Haryanto, A., Triyono, S., and Wicaksono, N.H. (2018) Effect of Loading Rate on Biogas Production from Cow Dung in A Semi Continuous Anaerobic Digester. Int. Journal of Renewable Energy Development, 7(2), 93-100.https://doi.org/10.14710/ijred.7.2.93-100